3D printing for polymer/particle-based processing: A review. (15th October 2021) - Xu, Weiheng; Jambhulkar, Sayli; Zhu, Yuxiang; Ravichandran, Dharneedar; Kakarla, Mounika; Vernon, Brent; Lott, David G.; Cornella, Jeffrey L.; Shefi, Orit; Miquelard-Garnier, Guillaume; Yang, Yang; Song, Kenan
Abstract: The 3D printing method, alternatively known as additive manufacturing (AM), is promising for rapid tooling and layered micromanufacturing. However, significant fundamental research and applied study in the 3D printing area are still necessary to develop new manufacturing mechanisms for combining multi-materials for multiscale and multi-functionality behaviors. Among those materials, particles with unique mechanical, thermal, electrical, optical, and other functional properties can find broad applications in structural composites, thermal packaging, electrical devices, optoelectronics, biomedical implants, energy storage, filtration, and purification. This review will first briefly cover the 3D printing basics before presenting the critical factors in polymer/particle-based printing. We will then introduce a spectrum of different printing mechanisms, i.e., vat polymerization-based, jetting-based, material extrusion-based, powder bed fusion-based, and a few other less utilized 3D printing methods, with a summary of the processing parameters, advantages, disadvantages, and future challenges of each printing technique. During this discussion of 3D printing, we will also present generally used polymers and particles, namely, liquid monomers, viscous inks, compliant gels, stiff filaments, and loosely packed pellets containing micro and nanoscale particles. The emphasis of this review is on the general printing mechanisms applicable in particle- and polymer-relevant processing. To end, this review identifies provides future perspectives regarding some new application examples. Identifying challenges in materials science and manufacturing processes will give direction to the fabrication of multifunctional systems for diverse applications, especially when using multi-materials (e.g., polymers and particles) at multiple scales (e.g., nanoscale morphologies and macroscale structures) for multifunctional systems.